Radiographic progression and remission rates in early rheumatoid arthritis – MRI bone oedema and anti-CCP predicted radiographic progression in the 5-year extension of the double-blind randomised CIMESTRA trial. Issue 10 (5th May 2010) - Hetland, Merete L; Stengaard-Pedersen, Kristian; Junker, Peter; Østergaard, Mikkel; Ejbjerg, Bo J; Jacobsen, Søren; Lottenburger, Tine; Hansen, Ib; Tarp, Ulrik; Andersen, Lis S; Svendsen, Anders; Pedersen, Jens K; et al.
Abstract : Objective: At 5 years' follow-up of early (<6 months) rheumatoid arthritis patients to (1) investigate whether initial combination therapy with methotrexate (MTX) and ciclosporin (CSA) (n=80) is superior to initial monotherapy with MTX (n=80) with respect to prevention of radiographic progression, (2) investigate whether the favourable clinical and radiographic response reported at 2 years in the CIMESTRA trial can be maintained and (3) identify predictors of radiographic outcome. Methods: 139 patients completed 5 years' follow-up with maintained double-blinding and a strict synovitis suppressive treatment strategy with intra-articular betamethasone injections (intra-articular glucocorticosteroid (GC)) and escalation of disease-modifying anti-rheumatic drug treatment. Disease activity, total Sharp-van der Heijde Score (TSS) of hands, wrists and forefeet were assessed at baseline and after 3, 4 and 5 years. MRI of the wrist and anti-cyclic citrullinated peptide (anti-CCP) were assessed at baseline. Results: At 5 years, TSS progression rate was <1 unit/year and 47% had not progressed radiographically since baseline. 78% were in Disease Activity Score remission, 56% in American College of Rheumatology remission and 17% withdrawn from treatment due to remission. There were no differences between initial treatment groups. MRI-bone marrow oedema, TSS and anti-CCP predicted radiographic progression at 5 years. Conclusion: Early and strict synovitis suppressive treatment with MTX and intra-articular GC lead to high remission rates and halting of erosive progression at 5 years. No additional effect of initial combination therapy with CSA was found. The results parallel those reported for tumour necrosis factor α antagonists. Baseline MRI-bone oedema, TSS and anti-CCP predicted radiographic progression.